Magnetism in geometrically frustrated YMnO3 under hydrostatic pressure studied with muon spin relaxation. - Lancaster, T; Blundell, S; Andreica, D; Janoschek, M; Roessli, B; Gvasaliya, SN; Conder, K; Pomjakushina, E; Brooks, M; Baker, P; Prabhakaran, D; Hayes, W; et al. (2007)
The ferroelectromagnet YMnO3 consists of weakly coupled triangular layers of S=2 spins. Below T(N) approximately equal to 70 K muon-spin relaxation data show two oscillatory relaxing signals due to magnetic order, with no purely relaxing signals resolvable (which would require different coexisting spin distributions). The transition temperature T(N) increases with applied hydrostatic pressure, even though the ordered moment decreases. These results suggest that pressure increases both the exchange coupling between the layers and the frustration within the layers.